Vaginal infections by Candida: Diagnosis and treatment - Ciudad Reynaud, Antonio (2015)
Vaginal infections are important cause of consultation as the only symptom or accompanied by other problems of different relevance. Depending on investigation series candidiasis represents the first or second place in the differential diagnosis of the different causes of vulvovaginal disturbances and vaginal discharge. In this article we review the epidemiology, risk factors, diagnosis and treatment.